RELEVANCE OF THE PROJECT METHOD IN STUDYING ENGLISH IN HIGHER SCHOOL - Корниенко, Людмила (SWorldJournal, 2020)
In the article the author analyzes the project method as one of the effective methods in studying a foreign language in a higher education institution. According to the author, this method meets the modern requirements, which are set before the High Schoo